Pathological complete response to neoadjuvant therapy with serplulimab and chemotherapy in stage IIIB small cell lung cancer: a case report and literature review - Mei, Ting; Wang, Ting; Lei, Chuanfen; Jiang, Dan; Zhou, Qinghua (Frontiers in Immunology, 2024)
Chemotherapy combined with immunotherapy has significantly improved survival in patients with extensive-stage small cell lung cancer (ES-SCLC), and neoadjuvant immunotherapy combined with chemotherapy has emerged as the standard treatment for those with resectable non-small cell lung cancer (NSCLC). However, the potential benefits of surgery following neoadjuvant immunotherapy combined with chemotherapy in locally advanced SCLC remain unclear. Herein, we report a patient diagnosed with stage IIIB SCLC, who was administered five cycles of neoadjuvant serplulimab combined with chemotherapy followed by surgery, and subsequently achieved a pathologic complete response (pCR). Within a follow-up duration of six months, the patient displayed neither recurrence nor metastasis and experienced no treatmentrelated adverse reactions of any grade. Based on this case, for locally advanced SCLC, neoadjuvant serplulimab combined with chemotherapy followed by surgery may present an effective, safe, and potentially curative treatment strategy. Nonetheless, further prospective studies are needed to verify our findings.